2017
DOI: 10.1007/s10792-017-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and agreement of central corneal thickness measurement with non-contact methods: a comparative study

Abstract: AS-OCT underestimated CCT measurements when compared to other two devices in healthy subjects. Hence, one must be cautious when analyzing the results from different machines and should be aware that the measurement values are not interchangeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Using the same devices, we found lower mean CCT with AL-scan and Sirius Topographer, which was 507.43 ± 33.54 and 512.08 ± 33.1 μm, respectively, in 127 healthy eyes (mean age, 35.91 + 7.7 years). [ 2 ] The present study[ 1 ] found a mean difference of 19.759 for CCT measurement and poor agreement with 95% limits of agreement (LoA) to be 17.220–22.299 ( P = 0.00) between the 2 devices. Our study reported a mean difference of − 4.6 μm for CCT and high level of agreement (95% LoA: -12.2 to 2.9, P = 0.26) between the 2 devices.…”
mentioning
confidence: 59%
“…Using the same devices, we found lower mean CCT with AL-scan and Sirius Topographer, which was 507.43 ± 33.54 and 512.08 ± 33.1 μm, respectively, in 127 healthy eyes (mean age, 35.91 + 7.7 years). [ 2 ] The present study[ 1 ] found a mean difference of 19.759 for CCT measurement and poor agreement with 95% limits of agreement (LoA) to be 17.220–22.299 ( P = 0.00) between the 2 devices. Our study reported a mean difference of − 4.6 μm for CCT and high level of agreement (95% LoA: -12.2 to 2.9, P = 0.26) between the 2 devices.…”
mentioning
confidence: 59%
“…However, this is not a major lack as high repeatability and reproducibility of those devices were confirmed by the previous studies. 8,9,11,13,14,16 The second limitation of this study is that we did not evaluate the CCT in patients with corneal diseases such as keratoconus, post-contact lens wear, and post-refractive surgery. The results could be different in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Normal reference values represent an essential base of clinical judgment for the patients. Once the normal range of CCT is speci ed in a population, applicable studies can be completed without the necessity for a control group, and patients' pachymetry analyses can be adjudicated with more certainty [18][19][20][21]. Still, most ophthalmic diagnostic instruments produced in America and Europe use normal reference values of their populations.…”
Section: Discussionmentioning
confidence: 99%